A Comparison of Smooth and Microtextured Breast Implants in Breast Augmentation: A Retrospective Study - Lee, Joo Hyuck; Jang, Jae Hyuk; Min, Kyung Hee (Archives of Plastic Surgery, 2023)
Background The number of cosmetic and reconstructive surgeries that use breast implants is increasing in Korea. Recently, it has been reported that breast implant-associated anaplastic large-cell lymphoma is related to textured breast implants, and interest in classification according to the texture of breast implants is increasing. However, there is currently no clear and unified classification. In particular, the definition of “microtextured” is highly varied. In this study, we retrospectively investigated and analyzed the clinical outcomes of smooth and microtextured breast implants.Methods A retrospective chart review of all patients who underwent breast augmentation surgery with smooth and microtextured silicone gel implants between January 2016 and July 2020 was performed. We retrospectively analyzed implant manufacturer, age, body mass index (BMI), smoking status, incision location, implant size, follow-up period, complications, and reoperation rate.Results A total of 266 patients underwent breast augmentation surgery, of which 181 used smooth silicone gel implants and 85 used microtextured silicone gel implants. Age, BMI, smoking status, implant size, and follow-up period were not significantly different between the two groups. Similarly, complications and reoperation rates were not significantly different between the two groups.Conclusion It is important to provide information regarding the clinical risks and benefits of breast implants to surgeons and patients through a clear and unified classification according to the texture of the breast implant.
Keywords: breast implants; mammaplasty; complications